Mappae Mundi Humans and their Habitats in a Long-Term Socio-Ecological Perspective, Myths, Maps and Models - Goudsblom, Johan; de Vries, Bert (Amsterdam University Press, 2002)
Never before in history was the interaction between people and their natural environment as complex and problematic as it is today. A proliferation of scientific research has yielded valuable insights into various aspects of this interaction from the angle of many disciplines - the natural sciences, the social sciences, archaeology and history, ecological studies. The diversity of approaches has created a need for synthesis, for a study that transcends the boundaries of traditional fields of study. In this volume, authors from various academic backgrounds discuss the relations between human society and its physical environment in the course of history, highlighting a number of significant periods, throughout the world. The last chapter assesses our present situation and prospects for the future in the light of theoretical reflections based on the evidence from the past.